Posztmodern: a modernizáció kritikája avagy új kihívás - Faragó, László (Tér és Társadalom, 1991)
This paper discusses the issue of the crisis of modernism and tries to find the regional aspects of this crisis through the synthesis of the different postmodern concepts. According to its hypothesis, fundamental changes take place in socio-economic development, and thus the character and quality of these regional processes also change. The crisis of modernism may mean the death of modern regional development, as well. Urbanization is a form of appearance of modern age, thus it is age-specific. Recent phenomena, and the developing new tendencies are not the integrated part of modern urbanization any more, but rather they refer to the appearance of a new course of development. The third desurbanizational phase of the urbanization process is not a transitional period any more, and it is not followed by the fourth phase. Before discussing the characteristics and crisis of modern regional development, the author calls our attention to the numerous common characteristics of the two most typical modernization models (state capitalistic and Lenin-Stalin-type) of the 20th century. Both of these models tried to create uniform national state on the bacis of hegemonistic development theory. The engine of their centrally controlled and directed system was created by the (industrial) corporations. The "producers" of both of these development courses thought that, with some corrections, their model can be applied to any cultural medium, and tried to export their model. Besides others, the reasons of the failure of modern regional-development policies are the following: Modern regional-development policy is based on the relatively uniform and successful model of early industrialization and urbanization. Development was identified with quantitative growth. Financial and other material requirements, and the importance of capital and mobility were emphasized, and the social, political, ecological, qualitative and structural characteristics of development were neglected. Local resources were evaluated according to universal, external aspects, which often resulted in ruthless exploitation or under-use. The practice of regional development was realized through vertical large organizations. Underdeveloped areas were usually supported with regional export, which acted against the exploration of internal resources and restructuring. As a result, no self-supporting tendencies developed. Modernism is not capable of solving the actual problems, thus it has reached the end of its development capacity. Postmodernism is not a new phase of modern era, because it did not put the emphasis on the negation, exceeding and overbidding of the previous, but rather it is based on a completely different historical consciousness. Postmodern movement is detotalizing, it refuses the external, forced normativism of modernism, and declares war on one-sided rationality. It is neither anti-political, nor politics-free. Postmodern tolerance and solidarity carries cosmopolitanism in a positive sense. Postmodernists consider space a practical political construction. All over the world, the process of urbanization developed as a result of modern capitalist development. The constructive and destructive forces of this huge energy still prevail, homogenization is a still-existing chance/danger, but we have to calculate with the strengthening of different, new phenomena. A specific pluralism takes place. Economy plays an ever decreasing role in the transformation of spatial structure. In stead of the rules of industrial civilization, regional limits are rather formed as a consequence of the mutual influence of culture and politics. This process is not part of the well-known urbanization any more, but it is something different. Space does not only mean "objective" conditions and gives spatial frameworks, but in stead, the interpretation of spatiality is also very important. Laws do not exert their influence in general, but according to geographical, temporal, social, etc. specificities. The role of "regionality", especially that of locality, increases. Both as abstractions and in concrete, these are given greater emphasis as compared to the national and international levels. They are important as the specific spheres of realization of glObal mechanisms, and the selection of certain values and truths can take place only at this regional levei. A part of the regionally separated communities can change for a postmodern way of development, while others stay with modernization. It has to be supposed in regional development as well, that certain communities can act and live "against" the megatrends. Completely different models can be realized side by side. Modern era brought about the "external explosion" of commodity and financial relations, of technology and technique, and results (resulted) in the differentiation of Lebensraum, while postmodernism results in the "internal explosion" dal! the limits, where bilateral contradictions are eliminated, and at the same time it acts against traditional differentiation. From the point of view of regional development, the fundamental issue of postmodernism is, that the world cannot be divided, and the different phenomena cannot be separated according to being modern/developing/developed, or pre-modern/backwarded/ underdeveloped. Countries of the third world are primarily different, and their backwardedness cannot be interpreted so easily as it is often done by many, according to the norms of modern consumer society. Under postmodern conditions, development should not necessarily start from the very same regions and growth poles or innovation centers. Different types of development may start simultaneously in different regions. Spatial movement of growth centers will expectedly speed up. Together with the changes of general conditions, a change in paradigma has been taking place in regional development since the 1970s. New, altemative concepts of regional development appeared: local (community) economic development, development from below, self-reliance, etc. New policies recommend local, regional development, which basically mobilize the regions’ internal resources, and prefer the regional integrity and self-management of local complex systems.